A retrospective evaluation of furosemide and mannitol for prevention of cisplatin‐induced nephrotoxicity. (9th March 2017) - Mach, C. M.; Kha, C.; Nguyen, D.; Shumway, J.; Meaders, K. M.; Ludwig, M.; Williams‐Brown, M. Y.; Anderson, M. L.
Summary: What is known and objective: Nephrotoxicity is a recognized side effect of cisplatin chemotherapy. However, the optimal strategy for preventing cisplatin‐induced nephrotoxicity, if any, remains unclear. The primary objective for this study was to determine whether mannitol or furosemide provides better nephroprotection when administered with hydration prior to weekly, low‐dose cisplatin concurrently with whole pelvic radiotherapy. Methods: Clinical data were abstracted from all women who underwent chemoradiation for FIGO IB2‐IVA cervical cancer at a regional safety net health system between January 2009 and December 2014. Creatinine clearance was estimated using the IDMS‐traceable MDRD Study Equation. Descriptive statistics were used to summarize patient demographics. Cox proportional hazard models were used to identify factors associated with hypomagnesemia and survival. Results and discussion: A total of 133 women received 656 weekly doses of single‐agent cisplatin (40 mg/m 2 ) concomitant with whole pelvic radiation. Furosemide (20 mg) was administered intravenously prior to 341 cisplatin doses, whereas mannitol (24 g) was administered prior to 315 doses. Significant magnesium wasting was observed after the second weekly cisplatin infusion regardless of whether furosemide or mannitol was utilized. Repetitive low‐dose cisplatin infusion had no impact on measured levels of serum creatinine or estimated glomerular filtration rate. Prior history of hypertension, diabetes mellitus, hepatitis C infection and acute gastrointestinal toxicity were each associated with early onset of hypomagnesemia. What is new and conclusions: Repetitive administration of low‐dose cisplatin concurrent with whole pelvic radiation is associated with magnesium wasting. However, choice of diuretic with pretreatment hydration had no significant impact on the severity of this adverse effect. Abstract : We have retrospectively reviewed the use of mannitol and furosemide prior to the administration of sensitizing doses of cisplatin in women undergoing treatment for locoregionally advanced cervical cancers. This data reveal that hypomagnesemia is the most common side effect experienced by these patients, typically appearing by the third dose of chemotherapy. Choice of diuretic has no impact on the incidence of severity of hypomagnesemia experienced.